OPTIMALISASI PENGENDALIAN KUALITAS PRODUK PALET KAYU MELALUI PENDEKATAN RCA & SPC - Zakaria, Tatan; Juniarti, Anita Dyah; Ramdani, Denis Muhamad; Sulistyo, Arif Budi (Prodi Teknik Industri, Fakultas Teknik, 2024)
This study aims to optimize the quality control of wood pallet products at PT. Azdhi Kayu Kreasi by using the Root Cause Analysis (RCA) and Statistical Process Control (SPC) approaches. The problem faced by the company is the high level of product defects that can reduce customer satisfaction and increase production costs. The RCA method is used to identify the root cause of product defects, while SPC is used to monitor and control the production process. Data were collected through field observations, interviews, questionnaires, and internal company documentation. The data were analyzed using P charts, Pareto diagrams, and fishbone diagrams. The results showed that the main cause of product defects was wood cracking, which was caused by factors such as poor raw material quality, production process errors, and unsuitable environmental conditions. The implementation of RCA and SPC proved effective in identifying and reducing the causes of product defects. By making improvements to the production process and selecting better raw materials, the product defect rate can be significantly reduced. This research makes a practical contribution to the company in improving product quality and production process efficiency.